2012
DOI: 10.1900/rds.2012.9.407
|View full text |Cite
|
Sign up to set email alerts
|

Islet Neogenesis: A Possible Pathway for Beta-Cell Replenishment

Abstract: ■ AbstractDiabetes, particularly type 1 diabetes, results from the lack of pancreatic β-cells. β-cell replenishment can functionally reverse diabetes, but two critical challenges face the field: 1. protection of the new β-cells from autoimmunity and allorejection, and 2. development of β-cells that are readily available and reliably functional. This chapter will examine the potential of endogenous replenishment of pancreatic β-cells as a possible therapeutic tool if autoimmunity could be blunted. Two pathways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 81 publications
3
45
0
2
Order By: Relevance
“…Several non-beta-cell types within the pancreas (duct, acinar, and alpha cells) and outside the pancreas (hepatocytes) have been demonstrated to possess the capacity to differentiate into beta-cells under different experimental conditions and/or following genetic manipulations in mice [9]. While these strategies hold promise, the translation of neogenesis into the clinic has not been made [10,11]. With respect to transplantation, a clinical trial by Living Cell Technologies TM using encapsulated porcine islets in human subjects is underway [12].…”
Section: Introductionmentioning
confidence: 99%
“…Several non-beta-cell types within the pancreas (duct, acinar, and alpha cells) and outside the pancreas (hepatocytes) have been demonstrated to possess the capacity to differentiate into beta-cells under different experimental conditions and/or following genetic manipulations in mice [9]. While these strategies hold promise, the translation of neogenesis into the clinic has not been made [10,11]. With respect to transplantation, a clinical trial by Living Cell Technologies TM using encapsulated porcine islets in human subjects is underway [12].…”
Section: Introductionmentioning
confidence: 99%
“…Le rôle et l'identité de ces progéniteurs restent imprécis et controversés [52]. Les cellules ductales ne représentent pas un modèle idéal pour des stratégies d'expansion ou de transdifférenciation in vivo, étant impliquées dans le cancer pancréatique [53].…”
Section: Référencesunclassified
“…Currently, cadaveric islets are transplanted into the portal vein of the recipient patient, which is chosen because of its proximity to the liver and the advantage of minimal invasion. However, about half of the islets introduced into the liver die during or shortly after transplantation [91][92][93]. Transplantation studies with mice showed that the kidney capsule, peritoneum or omental pouch provide a permissive environment for pancreatic population maturation and function.…”
Section: Engraftment Of Psc-derived Pancreatic Population: When and Wmentioning
confidence: 99%